Structural systems bebaviour and design - Stavridis, Leonidas (Thomas Telford, 2010)
Promoting and underlining the importance of structural thinking, Structural Systems: Behaviour and Design will provide readers with a comprehensive understanding of the behaviour of a wide range of structural systems based on the load-carrying mechanisms involved.